Experimental Determination of Eutectic Liquid Compositions in the MgO‐SiO2 System to the Lowermost Mantle Pressures. Issue 18 (23rd September 2018) - Ozawa, Keisuke; Anzai, Miyuki; Hirose, Kei; Sinmyo, Ryosuke; Tateno, Shigehiko
Abstract: We have performed melting experiments on the MgO‐SiO2 binary system to 139 GPa in a diamond anvil cell. Both MgO‐MgSiO3 and MgSiO3 ‐SiO2 eutectic compositions were examined by textural/chemical characterizations of recovered samples. Results demonstrate that the MgO‐MgSiO3 eutectic becomes more enriched in MgO with increasing pressure and is close in composition to Mg2 SiO4 at the core‐mantle boundary (CMB) pressure. On the other hand, the MgSiO3 ‐SiO2 eutectic is more SiO2 ‐rich at higher pressure and exhibits SiO2 /(MgO + SiO2 ) = 0.66 at the CMB. These have profound implications for a large‐scale compositional stratification possibly formed upon solidification of a magma ocean. The MgO‐MgSiO3 eutectic liquid being more MgO‐rich than previously predicted suggests that only bridgmanite crystallizes up to 60 wt% solidification from a fully molten state of a pyrolitic lowermost mantle. In contrast, an SiO2 layer may develop when melting/crystallization occurs in rocky objects with silica‐rich enstatite‐chondritic compositions. Plain Language Summary: MgO‐SiO2 is the most important binary system to understand melting/crystallization processes in the Earth's crust and mantle as well as those in other rocky objects. Its melting phase relations, in particular, eutectic compositions, also have profound implications for a large‐scale compositional stratification possibly formed upon solidification of a magma ocean. However, the eutectic compositions in the MgO‐MgSiO3 and MgSiO3 ‐SiO2 systems have not been examined experimentally at the deep lower mantle conditions yet. Here we performed melting experiments and determined both of these eutectic compositions to 135 GPa, corresponding to the pressure at the bottom of the mantle, by a combination of high‐pressure‐temperature generation in a laser‐heated diamond anvil cell and textural/compositional characterization of recovered samples. The results demonstrate that the MgO‐MgSiO3 eutectic liquid is more MgO‐rich than previously predicted. It suggests that a large volume of MgSiO3 bridgmanite‐dominant‐layer may have formed during crystallization of a deep magma ocean and is possibly still preserved up to the present in the Earth's lower mantle. On the other hand, the MgSiO3 ‐SiO2 eutectic liquid implies that an SiO2 ‐phase‐rich layer could develop when extensive melting occurs in rocky objects with silica‐rich enstatite‐chondritic compositions. Key Points: Our DAC experiments determined the eutectic liquid compositions in both the MgO‐MgSiO3 and MgSiO3 ‐SiO2 systems up to the CMB pressure The MgO‐MgSiO3 eutectic liquid composition is close to Mg2 SiO4 at 135 GPa MgSiO3 bridgmanite crystallizes predominantly up to 60 wt% solidification from a fully molten mantle above the CMB